On the best approximation in the mean and overconvergence of a sequence of polynomials of the best approximation - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate one property of a sequence of polynomials of the best approximation in the mean related to the convergence in a neighborhood of every point of regularity of a function on the level line ∂ G R.